2021
DOI: 10.1029/2021jd034978
|View full text |Cite
|
Sign up to set email alerts
|

The Nature, Amplitude and Control of Microwave Attenuation in the Atmosphere

Abstract: Microwave (MW) attenuation plays a critical role in constructing communication networks. It also can be a useful tool in the meteorological and optical communities for radar and microwave imaging applications. Because most atmospheric constituents (large hydrometeors being an exception) are very small compared to MW wavelengths, data analysis is typically performed using conventional Rayleigh theory; however, some anomalous observations have proven difficult to explain. We present the results of the first syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…They concluded that in normal circumstances, the presence of charges on the particle enhances the scattering EM wave in the backward direction, however the scattering of EM wave relies on factors such as particle size, frequency and refractive index. The investigation of EM wave field scattered off a charged particle were also reported in [115], where the authors presented the numerical results demonstrating the potential to modify the scattering field of the EM wave by adjusting the particle's surface potential, while keeping the incident wavelength, refractive index, and temperature constant. Therefore, they proposed a mathematical expression for the surface electric potential and the relative refractive index of a charged particle in terms of the amplitude ratio and phase difference of the dispersed electric field's transverse components results.…”
Section: H Influence Of Charges On Sds Attenuation Modelsmentioning
confidence: 98%
“…They concluded that in normal circumstances, the presence of charges on the particle enhances the scattering EM wave in the backward direction, however the scattering of EM wave relies on factors such as particle size, frequency and refractive index. The investigation of EM wave field scattered off a charged particle were also reported in [115], where the authors presented the numerical results demonstrating the potential to modify the scattering field of the EM wave by adjusting the particle's surface potential, while keeping the incident wavelength, refractive index, and temperature constant. Therefore, they proposed a mathematical expression for the surface electric potential and the relative refractive index of a charged particle in terms of the amplitude ratio and phase difference of the dispersed electric field's transverse components results.…”
Section: H Influence Of Charges On Sds Attenuation Modelsmentioning
confidence: 98%
“…MEGs have been widely used as coating filters, and their reflection loss performance were well-studied [ [21] , [22] , [23] , [24] , [25] ], which indicates addition of magnetic materials can effectively reduce radar wave reflection of materials. When the MEG is used in a form of large-area aerosol, its radar jamming efficiency greatly depends on absorption and scattering functions of each MEG particles, which, however, cannot be obtained by traditional laminate-based measurement methods (such as vector network instrument) [ 26 , 27 ]. Currently, there are some experimental methods that can measure attenuation performance of large-area aerosol, but the absorption and scattering behaviors occurring on the surface and inside of a single particle are not easy to show through experimental methods, which makes it difficult to explain the attenuation mechanism in detail [ 13 , 28 ].…”
Section: Introductionmentioning
confidence: 99%